EGFR inhibitor, AG1478, inhibits inflammatory infiltration and angiogenesis in mice with diabetic retinopathy. (16th September 2018) - Ju, Xin; Yang, Xi; Yan, Tao; Chen, Huaicheng; Song, Zongming; Zhang, Zongduan; Wu, Wencan; Wang, Yi
Summary: Diabetic retinopathy (DR) is one of the most frequently occurring microvascular complications of diabetes. Recent evidence indicates that epidermal growth factor receptors (EGFRs) are critical pathogenic players in non‐neoplastic diseases, including diabetic cardiomyopathy and DR. However, the precise pathogenic mechanism of EGFR in DR has yet to be fully understood. In this study, we developed a type 1 diabetic early‐stage retinopathy mouse model using injections of streptozotocin and an oxygen‐induced end‐stage diabetic retinopathy (OIR) model characterized by hypoxia‐induced revascularization. We tested the hypothesis that the pathogenesis of DR can be reduced by the classic EGFR inhibitor, AG1478, in the mouse models. Our data indicated that treatment of AG1478 prevented retinal dysfunction, and reduced impairment of retinal structures as well as mitochondrial structures in retinal blood vessels in diabetic mice. Furthermore, AG1478 reduced neovascular tufts formation but had no effects on revascularization at the avascular sites when compared to untreated littermates in the OIR model. Our findings provide strong evidence that EGFR critically promoted retinal dysfunction, retinal structural impairment, and retinal vascular abnormalities in models of DR. We conclude that EGFR can be a potential important therapeutic target for treatment of DR.